2017
DOI: 10.1515/geochr-2015-0059
|View full text |Cite
|
Sign up to set email alerts
|

Pleistocene glaciations of the SE Altai, Russia, based on geomorphological data and absolute dating of glacial deposits in Chagan reference section

Abstract: Geomorphological evidence of at least two Pleistocene glacial epochsis noted within the Chagan-Uzun river basin, SE Altai. A review and analysis of all available absolute dates for reference Chagan section is presented. The highest correlation amongst all TL dates is observed for the lens of glacio-lacustrine sediments -the most suitable among glacial deposits for luminescence dating, and indicates its possible Middle Pleistocene age. IRSL dates obtained from feldspar indicate a Middle Pleistocene age of morai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Later, the use of a TL technique based on applying naturally saturated etalons [94] showed that the formation of the entire gray-colored strata of the Chagan moraines in this section occurred in the interval from 135 ± 15 to 58 ± 7 ka BP. Later research led the authors of [27] to the conclusion that the use of modern TL technologies for dating moraines is inappropriate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Later, the use of a TL technique based on applying naturally saturated etalons [94] showed that the formation of the entire gray-colored strata of the Chagan moraines in this section occurred in the interval from 135 ± 15 to 58 ± 7 ka BP. Later research led the authors of [27] to the conclusion that the use of modern TL technologies for dating moraines is inappropriate.…”
Section: Discussionmentioning
confidence: 99%
“…al. [27] studied the applicability of the TL method for the dating of glacial sediments in Chagan-Uzun. It was found out that the dating results of the same sample, performed in different laboratories, were very different, and both had poor agreement with the stratigraphic position of the samples in the section.…”
Section: Introductionmentioning
confidence: 99%
“…and are high enough for the formation of glaciers. The number and extent of Pleistocene glaciations remains a subject of discussion [24], and the middle-late Holocene glacier advance was inferred to have occurred in three events [2,25].…”
Section: Study Areamentioning
confidence: 99%
“…The high-mountain, south-eastern part of the Russian Altai (SE Altai, Figure 1), which is examined in this paper, is characterized by strongly dissected topography-the result of Cenozoic orogenesis [5,32,33]. Summits rise above the floors of intermountain depressions and major valleys up to 2600-3000 m, which is one of the largest values for the whole Altai Mountains system [33].…”
Section: Study Areamentioning
confidence: 99%